Social Media in Employee Selection and Recruitment Theory, Practice, and Current Challenges - Landers, Richard N.; Schmidt, Gordon B. (Springer International Publishing : Imprint: Springer, 2016)
This timely resource offers fresh research on companies' use of social media platforms-from Twitter and Facebook to LinkedIn and other career sites-to find and hire personnel. Its balanced approach explains why and how social media are commonly used in both employee recruitment and selection, exploring relevant theoretical constructs and practical considerations about their appropriateness and validity. Contributors clarify a confusing cyberscape with recommendations and best practices, legal and ethical issues, pitfalls and problems, and possibilities for standardization. And the book's insights on emerging and anticipated developments will keep the reader abreast of the field as it evolves. Included in the coverage: · Social media as a personnel selection and hiring resource: Reservations and recommendations. · Game-thinking within social media to recruit and select job candidates. · Social media, big data, and employment decisions. · The use of social media by BRIC nations during the selection process. · Legal concerns when considering social media data in selection. · Online exclusion: Biases that may arise when using social media in talent acquisition. · Is John Smith really John Smith? Misrepresentations and misattributions of candidates using social media and social networking sites. Social Media in Employee Selection and Recruitment is a bedrock reference for industrial/organizational psychology and human resources academics currently or planning to conduct research in this area, as well as for academic libraries. Practitioners considering consulting social media as part of human resource planning or selection system design will find it a straight-talking guide to staying competitive. .